Expropriation through related party transactions: the position in Malaysia - Chan, W.M. (2010)
Johnson et al (2000) explored instances of expropriation of wealth by controlling shareholders of a company from the minority shareholders, among which are the transfers of assets to other companies under the majority shareholders’ control and the extractions of cash through dubious transactions. With the amendment to the Companies Act 1965 in 2007, the rules pertaining to related party transactions in Malaysia have become more stringent. However, as shown in some recent reported transactions, the rules are not without weaknesses which may be exploited by the controlling shareholders to the detriment of the minority. This article provides a critical discourse on first, the law pertaining to related party transactions in Malaysia; and secondly, some recent cases in Malaysia where the controlling shareholders in companies expropriated wealth from the minority. This article will also make some recommendations to further tighten the rules on related party transactions.